NeuroPhilosophy and Free Will: Bridging Neuroscience, Philosophy, and Society in the Age of Neurotechnology - Ikrar, Taruna; Sophian, Alfi (Journal of NeuroPhilosophy, 2025)
The free will debate has long been central to philosophy, connecting metaphysical questions of autonomy with issues of moral and legal responsibility. With the advent of neuroscience, this debate has shifted from speculative theorizing to empirical investigation. NeuroPhilosophy, pioneered by Patricia Churchland and others, provides a framework that integrates brain science with philosophical analysis, offering new ways to understand the nature of agency. This article presents a narrative review of key developments from 1983 to 2025, synthesizing findings from experimental neuroscience, philosophical theories, and recent interdisciplinary discussions in neuroethics and artificial intelligence. Special attention is given to Libet’s readiness potential studies, predictive neuroimaging approaches, and alternative models such as stochastic accumulator frameworks. Beyond laboratory evidence, this review explores contemporary challenges including brain–computer interfaces, predictive AI, and their implications for law and society. The novelty of this work lies in proposing a “spectrum model of agency,” which situates free will not as a binary condition but as a dynamic construct shaped by neural, social, and technological factors. By bridging empirical findings with normative philosophy, this review demonstrates how NeuroPhilosophy can reframe the free will debate, ensuring its relevance in the age of neurotechnology and global ethical concerns.